The Place of Communication in Personal Life. - Turayeva Dildora Shuhratovna (Genius Publishing Group, 2022)
The article analyzes the multifaceted process of cooperation between people the devolepment of communication with them and the role of communication in the formation the spiritual imade of a person. Communication is unique to all living beings creatures and is most developed precisely human level. It was said the satisfaction of almost all the nedds of a person of a different kind is propess that saps on how well catered it is communication nedds. The analizing in communication of person has a lot of thinking goals and process of knowing the world
Keywords: Communication; language; needs; thinking